Analisis Rendahnya Minat Baca Siswa Kelas 4 di SD Negeri Cikampek Timur 1: Faktor-Faktor Penyebab dan Implikasinya dalam Konteks Pendidikan Dasar - Eka Mustikawati (International Forum of Researchers and Lecturers, 2024)
The low interest in reading among elementary school (SD) students poses a significant challenge in the context of primary education. This article identifies various factors that contribute to the low interest in reading among students, including lack of access to engaging reading materials, insufficient support from parents, lack of motivation or intrapersonal interest, uninteresting curriculum and teaching methods, influence of electronic media, socio-economic conditions, lack of reading role models, and difficulties in reading. The analysis yields recommendations that encompass improving access to engaging reading materials, encouraging parental support, fostering student motivation and intrapersonal interest, and developing engaging curriculum and teaching methods. Through a holistic and sustainable approach, it is hoped that these recommendations can help address the challenges of low reading interest among elementary school students and enhance the quality of literacy learning at the primary level.